2015
DOI: 10.1002/jbm.b.33401
|View full text |Cite
|
Sign up to set email alerts
|

Cooling rate effects on thermal, structural, and microstructural properties of bio‐hydroxyapatite obtained from bovine bone

Abstract: This article is focused on the study of cooling rate effects on the thermal, structural, and microstructural properties of hydroxyapatite (HAp) obtained from bovine bone. A three-step process was used to obtain BIO-HAp: hydrothermal, calcinations, and cooling. Calcined samples in a furnace and cooling in air (HAp-CAir), water (HAp-CW), and liquid nitrogen (HAp-CN2), as well as an air cooled sample inside the furnace (HAp-CFAir), were studied. According to this study, the low cooling rate that was achieved for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…The physicochemical properties of the isolated phase obtained by incineration depend on variables such as heating rate, annealing temperature, sintering time, cooling, and the atmosphere 6,8,9 . One of them is the crystal size that is commonly determined through X-ray diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…The physicochemical properties of the isolated phase obtained by incineration depend on variables such as heating rate, annealing temperature, sintering time, cooling, and the atmosphere 6,8,9 . One of them is the crystal size that is commonly determined through X-ray diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…The physicochemical characterization of raw bones and BIO‐HAps obtained through different methodologies is still an open problem due to their complexity. Infrared (IR) and Raman spectroscopies have been extensively used to study these materials, monitoring the removal of the organic matrix from the mineral phase, as well as to identify different mineral phases and to identify the changes in the crystalline quality of HAp caused by thermal processes . However, no studies about the influence of the crystal size on the vibrational properties (optical) of synthetic and BIO‐HAps have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Ramirez-Gutierrez et al 102 have studied the effect of coolant on microstructure properties of a bovine bone cooled under air, water, and nitrogen. It was found that cold air has flown away chips, but it has minimum potential to control the temperature elevation.…”
Section: Irrigation Techniquesmentioning
confidence: 99%